Bacterias patógenas para el hombre aisladas en productos agrícolas provenientes de la cuenca del Rio Guano. - Mishell del Rosario, Cazares Silva (2019)
At the global level, the water and food contamination is an emerging health problem. This study aims to identify bacteria of clinical interest identified from agricultural products irrigated with water from the Guano River, Chimborazo, Ecuador, determining their resistance and antimicrobial susceptibility. This is a descriptive, transversal, field, inductive and observational work. We measured the environmental temperature and altitude of the geographical site where the sample was collected. For the isolation and identification of microorganisms, culture resources such as peptonated water, blood agar. McConkey and interpretation of physiological and biochemical tests to classify the species, obtaining 16 bacterial strains. For the susceptibility measure and resistance, the Kirby Bauer technique was performed. The Enterobacteriaceae family was the most isolated (75%) with Citrobacter diversus, Citrobacter amalonaticus, Enterobacter aerogenes, Enterobacter cloacae, Hafnia alvei, while 18.75% corresponded to Aeromonadaceae (3 strains). The Streptococcaceae family (6.25%) with the genus Enterococcus as the only isolated positive Gram. The bacterial symptoms specified in this study are generally very sensitive to the antibiotics tested, except for Amoxicillin that presented 80% resistance and Enterobacter aerogenes (strain 3) presented multiresistance to Gentamicin. Kanamycin, Nalidixic Acid. Imipenem and Aztreonam. Phenotypicallv showing resistance to cephalosporins. The results indicate that the products studied are dangerous to human health, due to the increase in enteropathogens presented. It is recommended to socialize these results to the relevant authorities, in order to prevent intestinal or extraintestinal infections due to their consumption.